Panjang Siklus Estrus dan Struktur Histologi Ovarium Tikus Putih Setelah Pemberian Ekstrak Etanol Daun Kaliandra Merah - Mardika, Kadek; Setyawati, Iriani; Darmadi, Anak Agung Ketut (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
Red calliandra (Calliandra calothyrsus Meissn.) leaves contain chemical compounds such as flavonoids, tannins, and steroids. Previous research of C. calothyrsus leaf extracts showed effect on male mice reproduction, but no research has been done about its effect on estrous cycle and histology structure of albino rat ovary. This research aimed to study the potency of C. calothyrsus leaf extracts as phytoestrogen on the female reproductive organ through observing the estrous cycles, and histological structure and weight of the ovaries. Twenty four of 54-day-old female albino rats (Rattus norvegicus) Wistar strain were divided into four groups i.e. placebo control (given 0.5% Na-CMC solvent) and three treatment groups of C. calothyrsus leaf extracts in dosages 17.5; 35; and 70 mg/kg BW (respectively, group P1, P2 and P3). Treatments were administered orally in 1 ml/rat/day for 20 days. The vaginal smears were investigated from day 5th for 15 days (three estrous cycles). It was carried out every 8 hours/day.  At the end of the treatments, rats were dissected for collecting the ovaries. They were weighed and prepared histologically then by using paraffin method with Hematoxylin-Eosin staining. The parameters observed were ovary weight and histological structures, including the number of primary follicles, secondary follicles, tertiary follicles, de Graff follicles, corpus luteum, and atretic follicles. The results showed that C. calohtyrsus leaf extracts have a phytoestrogenic potency by shortened the proestrous and estrous phases, increased the corpus luteum number and decreased the ovarian weights significantly at dose 70 mg/kg BW.